Optimization of Aeration and Agitation Rate for Lipid and Gamma Linolenic Acid Production by Cunninghamella bainieri 2A1 in Submerged Fermentation Using Response Surface Methodology - Normah Saad; Peyman Abdeshahian; Mohd Sahaid Kalil; Wan Mohtar Wan Yusoff; Aidil Abdul Hamid (The Scientific World Journal)
The locally isolated filamentous fungus Cunninghamella bainieri 2A1 was cultivated in a 5 L bioreactor to produce lipid and gamma-linolenic acid (GLA). The optimization was carried out using response surface methodology based on a central composite design. A statistical model, second-order polynomial model, was adjusted to the experimental data to evaluate the effect of key operating variables, including aeration rate and agitation speed on lipid production. Process analysis showed that linear and quadratic effect of agitation intensity significantly influenced lipid production process (P<0.01). The quadratic model also indicated that the interaction between aeration rate and agitation speed had a highly significant effect on lipid production (P<0.01). Experimental results showed that a lipid content of 38.71% was produced in optimum conditions using an airflow rate and agitation speed of 0.32 vvm and 599 rpm, respectively. Similar results revealed that 0.058 (g/g) gamma-linolenic acid was produced in optimum conditions where 1.0 vvm aeration rate and 441.45 rpm agitation rate were used. The regression model confirmed that aeration and agitation were of prime importance for optimum production of lipid in the bioreactor.